Penyuluhan Perencanaan Keuangan Keluarga Bagi Ibu-Ibu PKK Desa Pekuncen Kecamatan Jatilawang Kabupaten Banyumas - Agung Prayogi (LPPM Stikosa - AWS, 2024)
Family financial planning counseling for PKK women in Pekuncen Village, Jatilawang District, Banyumas Regency aims to provide knowledge and understanding of the importance of financial planning in the family so that they are able to manage family income and expenses appropriately. Through counseling, PKK women were given material on why planning is necessary, what is financial planning, how to plan family finances, which is more important for you, evaluating financial health and the benefits of family financial planning. The results of this counseling received positive responses from PKK women because it provided knowledge and understanding to PKK women about financial planning in the family. Family financial planning counseling has an important role in providing knowledge and understanding to PKK women in managing and planning family finances.